Intermediate and high-risk non-muscle-invasive bladder cancer: an overview of epidemiology, burden, and unmet needs - Grabe-Heyne, Kristin; Henne, Christof; Mariappan, Paramananthan; Geiges, Götz; Pöhlmann, Johannes; Pollock, Richard F. (Frontiers in Oncology, 2023)
Bladder cancer ranks among the most common cancers globally. At diagnosis, 75% of patients have non-muscle-invasive bladder cancer (NMIBC). Patients with low-risk NMIBC have a good prognosis, but recurrence and progression rates remain high in intermediate- and high-risk NMIBC, despite the decades-long availability of effective treatments for NMIBC such as intravesical Bacillus Calmette-Guérin (BCG). The present review provides an overview of NMIBC, including its burden and treatment options, and then reviews aspects that counteract the successful treatment of NMIBC, referred to as unmet treatment needs. The scale and reasons for each unmet need are described based on a comprehensive review of the literature, including insufficient adherence to treatment guidelines by physicians because of insufficient knowledge, training, or access to certain therapy options. Low rates of lifestyle changes and treatment completion by patients, due to BCG shortages or toxicities and adverse events as well as their impact on social activities, represent additional areas of potential improvement. Highly heterogeneous evidence for the effectiveness and safety of some treatments limits the comparability of results across studies. As a result, efforts are underway to standardize treatment schedules for BCG, but intravesical chemotherapy schedules remain unstandardized. In addition, risk-scoring models often perform unsatisfactorily due to significant differences between derivation and real-world cohorts. Reporting in clinical trials suffers from a lack of consistent outcomes reporting in bladder cancer clinical trials, paired with an under-representation of racial and ethnic minorities in many trials.